Electrochemical and Spectroelectrochemical Properties of Poly(carbazole-EDOT)s Derivatives Functionalized with Benzonitrile and Phthalonitrile Units. (1st January 2016) - Hu, Bin; Luo, Wen; Jin, Lin; Liu, Zengchen; Wang, Mengnan; Zhou, Liuyang; Li, Chunyang
Abstract : Two novel carbazole-3, 4-ethoxylenedioxythiophene (EDOT) derivatives containing acceptor groups such as benzonitrile and phthalonitrile were synthesized and characterized. Both the monomers could be electrochemically polymerized and form stable electroactive polymer films. Spectroelectrochemical technique were performed to investigate the electrochemical and optical changes of the resulting polymer films, multi-electrochromic properties upon different applied potentials suggested the effect of the benzonitrile and phthalonitrile units and their potential applications in electrochromic device. Furthermore, scanning electron micrographs (SEM) were used to study the microstructure morphology of polymer films.